PRINSIP 6C (CHARACTER, CAPACITY, CAPITAL, CONDITION OF ECONOMY, COLLATERAL DAN CONSTRAINT) DALAM WIRAUSAHA MAHASISWA - Henny Sri Astuty (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2015)
Abstrak: Prinsip 6C (Character, Capacity, Capital, Condition of Economy, Collateral dan Constraint) dalam Wirausaha Mahasiswa. Kegiatan wirausaha yang sekarang banyak dilakukan oleh mahasiswa memiliki sisi positif maupun negatif, dari yang berhasil kuliah dan wirausahanya hingga yang gagal semuanya. Untuk ini diperlukan pemahaman tentang prinsip enam C (character, capacity, capital, condition of economy, collateral and constraint) yang akan membantu mahasiswa sebagai bekal dalam melakukan kegiatan usahanya. Banyak faktor yang diperoleh dalam prinsip ini yaitu aspek manajemen, pemasaran, produksi, dan keuangan.Kata Kunci: prinsip 6c, wirausaha, mahasiswaAbstract: 6C Principles (Character, Capacity, Capital, Condition of Economy, Collateral and Constraint) in Entrepreneurial Students. Entrepreneurial activity that is widely performed by students has two different stories. Some of them are successful on the other hand, the rest of them are fail. Accordingly, it is required an understanding of the 6C principles of the six C (character, capacity, capital, condition of economy, collateral and constraints) which will help the students as a preparation in conducting their business activities. Many factors obtained in this principle namely: management, marketing, production, and financial aspects. Keywords: 6C principles, entrepreneurs, students